Optimalisasi Minyak Jelantah dan Sumber Daya Alam Atsiri sebagai Lilin Aromaterapi dan Sabun Wangi Atsiri di Desa Nglebak, Tawangmangu, Karanganyar, Jawa Tengah - Afif Damar Pratisto; Qosrul Karimah; Priyanka Khansa Insyira; Vito De Caprio Matius Hutabalian; Rocky Kencana Putra; Oca Higiawati; Gayatri Sitoresmi; Rissa Kurnia Anggraini; Suryadi Budi Utomo (Lembaga Pengembangan Kinerja Dosen, 2024)
One common household waste often encountered and rarely processed is used cooking oil. Used cooking oil is the residual oil from frying that has been repeatedly used. The common practice of reusing or improperly disposing of it by the community is considered hazardous as it has the potential to poison the body and pollute the environment. One effort to utilize used cooking oil is by recycling the waste into raw materials for making aromatherapy candles and essential oil scented soaps. This purpose activity is empower the community of Nglebak to utilize household waste and transform it into economic materials. This activity is carried out through research methods, material presentation, processing practice, and discussion. The research results on aromatherapy candles indicate that a formulation of used cooking oil and coconut wax at a ratio of 2:1 can produce ecofriendly aromatherapy candles with an ideal appearance and duration. The research results on soap indicate that stirring for 30 minutes with a volume of 60 mL of KOH (Potassium Hydroxide) is the ideal formulation for making essential oil scented soaps as it yields the most with a pH that complies with SNI No. 40-4058-1996